PENGARUH MANAJEMEN DAN BUDAYA KERJA TERHADAP PENINGKATAN KINERJA USAHA KECIL MENENGAH (UKM) TULIP CRAFT - Kurniasari, Ana Aprillia; Sari, Citra Mulya (Universitas Nusa Cendana, 2024)
This study aims to determine the effect of Management and Work Culture on Performance Improvement in Tulip Craft. The sampling technique in this study used Cluster Sampling. The samples taken were 64 Tulip Craft employees in Tulungagung. The study results show that the Management and Work Culture variables partially or simultaneously significantly affect Performance Improvement in Tulip Craft. Keywords: Management; Work Culture; Performance Improvement